Designing an information system for recapitulating goods received transactions - Radiyatul Ulia; Didin Setyawan; Afrina (Journal of Computer-based Instructional Media, 2024)
This research aims to design and implement an information system to recapitulate goods receipt and delivery transactions. Previously, this process used Microsoft Excel, which required manual data copying, took a long time, and required daily, weekly, and monthly printing and reporting. In addition, the application used was not stored in a database and was not integrated with the network, making data processing inefficient. In order to overcome this problem, the research developed a database programming-based information system with the waterfall method for the design stage. System modelling is done with the Unified Modeling Language (UML). This research produces a needs analysis, system design using UML, and nine tables supporting the system. Testing is done with black box testing and direct trials by users involved in data management, showing satisfactory results. Implementing the system using PHP programming and MySQL database resulted in a web-based application that accelerates the recapitulation process, stores data in the database, and is integrated with the network. This application is proven to speed up data processing. The application needs to be improved with more complex technology and compatible with various smartphones for further development. In addition, the app needs a dashboard feature to display the number of daily monthly deliveries, as well as the income of each officer. Increasing the number of human resources capable of maintaining the system is also important to ensure its sustainability and efficiency.